2006
DOI: 10.1211/jpp.58.7.0001
|View full text |Cite
|
Sign up to set email alerts
|

Role of CYP pharmacogenetics and drug-drug interactions in the efficacy and safety of atypical and other antipsychotic agents

Abstract: Cytochrome P450 (CYP) drug oxidases play a pivotal role in the elimination of antipsychotic agents, and therefore influence the toxicity and efficacy of these drugs. Factors that affect CYP function and expression have a major impact on treatment outcomes with antipsychotic agents. In particular, aspects of CYP pharmacogenetics, and the processes of CYP induction and inhibition all influence invivo rates of drug elimination. Certain CYPs that mediate the oxidation of antipsychotic drugs exhibit genetic variant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(68 citation statements)
references
References 146 publications
0
67
0
1
Order By: Relevance
“…Prodrugs such as tramadol, tilidine, or risperidone, mainly metabolized by one or two isoenzyme, could lose their potency, if bioactivation was blocked (Mannheimer et al, 2008;Stamer et al, 2007;Wustrow et al, 2012). Neuroleptics such as clozapine or haloperidol could accumulate in plasma and lead to toxic concentrations (Murray, 2006). The inhibition of CYP2D6 and CYP3A4 could be important because many endogenous compounds and xenobiotics were metabolized by these two isoenzymes (http://medicine.iupui.edu/clinpharm/ddis/clinical-table/).…”
Section: Discussionmentioning
confidence: 99%
“…Prodrugs such as tramadol, tilidine, or risperidone, mainly metabolized by one or two isoenzyme, could lose their potency, if bioactivation was blocked (Mannheimer et al, 2008;Stamer et al, 2007;Wustrow et al, 2012). Neuroleptics such as clozapine or haloperidol could accumulate in plasma and lead to toxic concentrations (Murray, 2006). The inhibition of CYP2D6 and CYP3A4 could be important because many endogenous compounds and xenobiotics were metabolized by these two isoenzymes (http://medicine.iupui.edu/clinpharm/ddis/clinical-table/).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the CYP1A2 substrate caffeine might have an influence-there have been several reports that ingestion or removal of caffeine containing beverages influenced concentrations of the CYP1A2 substrate clozapine. 40 Our patients, however, had been hospitalized and were on a standard diet which did not contain major amounts of these foods. An unusual exposure to and influence of alimentary inducers is, therefore, unlikely.…”
Section: -Htr2c C-759tmentioning
confidence: 99%
“…18 These strategies are commonplace in psychopharmacology and have been used in several pharmacogenetic studies. 19,20 This pharmacogenetic study revealed an association of risperidone-induced EPS with rs167771, a common genetic variant in the third intron of the DRD3 gene. The D3 receptor was cloned and characterized as a D2-like receptor in 1990.…”
Section: Discussionmentioning
confidence: 90%